Vibrio cholerae O1 Avirulent Strains - Producers of Protective O1 Antigen: Obtaining and Peculiarities - E. N. Strelnikova-Aab; L. F. Livanova; A. A. Goryaev; N. B. Cheldyshova; N. I. Smirnova (Проблемы особо опасных инфекций, 2010)
Among 15 Vibrio cholerae El Tor O1 virulent strains of Inaba and Ogawa serovars grown in sterile river water, 6 strains were found to lose spontaneously the core region of CTXφ prophage including structural genes (ctxAB) of cholera toxin. It was determined that the obtained ctxA- mutants did not produce cholera toxin and did not cause specific choleragenic reaction in the intra-intestinally inoculated suckling rabbits suggesting that they belonged to the IIId pathogenicity group. Analysis of the population structure of two selected non-toxigenic strains M569A and 5/65A revealed clones with high level of O1 antigen of Inaba and Ogawa serovars production. The obtained avirulent strains can be used as producers of above-noted protective antigens both in production of chemical cholera vaccine and in constructing of diagnostic immunoenzyme test-systems.